Du désir d’autonomie à l’indépendance - Marie-Christine Bureau; Antonella Corsani (La Nouvelle Revue du Travail)
The “self-employed” constitute a highly heterogeneous statistical category. The present article argues that a significant recent increase in their numbers translates a sea change in today’s production and/or work paradigms. The patterns of the “independent workers” who have been emerging specifically mirrors those generally associated with skilled service sector workers. Products of the crisis in wage-earning, these individuals also incarnate the new demand for autonomy. After using a historical perspective to demonstrate the diversity of self-employed workers and their changing situations, certain assumptions are made both about the meaning of these new worker archetypes - ones who have emerged out of the space between coercion and the desire for autonomy – and the forms of collective action they embody.